Self-Access Language Learning: Students' Perceptions of and Experiences Within this New Mode of Learning - Luz Edith Herrera Díaz (Universidad Nacional de Colombia, 2012)
With the aim of fostering autonomy in learning, both innovations, the self-access centre and the mode of learning derived from it, were adopted in the context of the study (Language Centre in the University of Veracruz, Mexico). Based on a case study, I have adopted a qualitative perspective to do this research, which aimed to know how the students undergoing this new English learning mode perceived it and what their experiences were within the no-class courses. The purpose of this article is to present the main themes that emerged after gathering the data for this study. It concludes with suggestions for a more contextualized and critical adoption of innovations in the English as a Foreign Language arena.